Cinema e animação: poéticas de um vivência - Brandão, Flávia Christina Leite (2013)
This study aimed to mix in the work art experience theory and poetics. Were aggregated at the same level both religious and visual references of the author to produce a short film hybrid between live-action film and animation. The study of the archetypes Umbanda’s entities and the history and principles of animation also contributed, like the film hybrid between film and animation and analysis of the film Kill Bill I, chosen as the reference technique with which we bond our poetic. In the theoretical chapter the history of animation is based on the principles of technological devices of the season coming to current devices such as computers and software that were of great importance to the animation frame by frame made by the author. The choice of technique animated 2D is closely linked to technological devices today. We base ourselves on the theories of film analysis to conduct the analysis of Tarantino's movie and through this stimulus did correlate with in our practice we get elements of great importance for the production of the short film. Added to this analysis we also identify the archetype of character O'Ren Ishii that served us for the construction of the archetypes of our characters, creating a fine line between Tarantino references and references of the author. All this added to the theory and practice experience led us to achieving a live-action film and animation drawing on inspirations on religious experiences and professional author culminating in the production sequence and performing a short film essentially copyright.